Lycopene Protects against Smoking-Induced Lung Cancer by Inducing Base Excision Repair - Junrui Cheng; Baxter Miller; Emilio Balbuena; Abdulkerim Eroglu (MDPI AG, 2020)
Background: Oxidative stress plays a critical role in lung cancer progression. Carotenoids are efficient antioxidants. The objective of this study was to explore the efficacy of all-trans retinoic acid (ATRA) and carotenoids in cigarette smoke-induced oxidative stress within A549 human lung cancer epithelial cells. Methods: A549 cells were pretreated with 1-nM, 10-nM, 100-nM, 1-μM and 10-μM ATRA, β-carotene (BC) and lycopene for 24 h, followed by exposure to cigarette smoke using a smoking chamber. Results: The OxyBlot analysis showed that smoking significantly increased oxidative stress, which was inhibited by lycopene at 1 nM and 10 nM (p < 0.05). In the cells exposed to smoke, lycopene increased 8-oxoguanine DNA glycosylase (OGG1) expression at 1 nM, 10 nM, 100 nM, and 1 μM (p < 0.05), but not at 10 μM. Lycopene at lower doses also improved Nei like DNA glycosylases (NEIL1, NEIL2, NEIL3), and connexin-43 (Cx43) protein levels (p < 0.05). Interestingly, lycopene at lower concentrations promoted OGG1 expression within the cells exposed to smoke to an even greater extent than the cells not exposed to smoke (p < 0.01). This may be attributed to the increased SR-B1 mRNA levels with cigarette smoke exposure (p < 0.05). Conclusions: Lycopene treatment at a lower dosage could inhibit smoke-induced oxidative stress and promote genome stability. These novel findings will shed light on the molecular mechanism of lycopene action against lung cancer.